Auckland Volcanic Field magmatism, volcanism, and hazard: a review. Issue 2 (3rd July 2021) - Hopkins, Jenni L.; Smid, Elaine R.; Eccles, Jennifer D.; Hayes, Josh L.; Hayward, Bruce W.; McGee, Lucy E.; van Wijk, Kasper; Wilson, Thomas M.; Cronin, Shane J.; Leonard, Graham S.; Lindsay, Jan M.; Németh, Karoly; et al.
ABSTRACT: Auckland Volcanic Field (AVF) is a basaltic intraplate volcanic field in North Island, New Zealand, upon which >1.6 million people live. Seismic velocity tomography and geochemistry suggest a primary mantle source region at a depth of 70–90 km. Geochemical analysis indicates a range of magma compositions, and that melts ascend with little crustal interaction. Eruptions generally began with a phreatomagmatic phase forming maar and tuff rings with tephra fall, base surges, and ballistic projectiles as the main hazards. Subsequent magmatic phases formed scoria cones, and sometimes produced lava flows. Ages of 47 of the 53 volcanic centres reveal that the AVF first erupted ∼193 ka, and last erupted ∼500 yrs. BP. These geochronological constraints indicate repose periods ≤0.1–13 kyr, which have decreased since ∼60 ka. From known geological and exposure information, and using an interdisciplinary approach, eight future eruption scenarios have been developed for planning processes. Outstanding questions for the AVF concern the cause of mantle melting, the structure of the underlying lithosphere, magma ascent rates, controls on repose periods and eruptive volumes. Answering these questions may improve our understanding of warning periods, monitoring strategies, spatiotemporal risk profiles, and socio-economic impacts of volcanism on New Zealand's largest city.